Effect of acute and chronic grapefruit, orange, and pineapple juice intake on blood lipid profile in normolipidemic rat. - Daher, Costantine F. (2005)
Background: High fruit intake is known to be associated with reduced riskof coronary heart disease. Our objective was to determine the effects of acute and chronic juice [grapefruit,orange, and pineapple] intake on plasma lipid profile and lipoprotein metabolism in normolipidemic rats.Material/Methods: The effects of acute juice intake were studied after three hours of a single juice-lipidload instilled intragastrically. In the chronic study, blood samples from fasted animals were subjectedto analyses after six months of either water [control] or water-juice [1:1] intake. Results: In the acutestudy, pineapple and grapefruit significantly decreased plasma triacylglycerol [TAG], and chylomicron[CM] TAG and cholesterol concentrations concomitantly with delayed gastric emptying. Plasma cholesterollevels and very-low-density lipoprotein [VLDL] secretion and metabolism were not affected. In the chronicstudy, only grapefruit significantly decreased plasma and VLDL TAG concentrations and relative VLDL particlesize with respect to other groups. All juices significantly increased VLDL apolipoprotein B [apoB] secretion,but plasma total apoB concentrations were highest in the grapefruit group and lowest in the orange andpineapple groups. No effect on blood cholesterol levels was observed. Conclusions: The cardioprotectivebenefit of chronic juice intake in normolipidemic rat may be chiefly through mechanisms independent ofa direct effect on blood lipid profile, although orange and pineapple, but not grapefruit, relativelyimproved the metabolism and clearance of blood lipoprotein particles. As a result of delayed gastricemptying, grapefruit and pineapple juices may moderate sharp increases in postprandial plasma TAG concentrationsaccompanying peak digestion and absorption.